Postnatal development of extracellular matrix and vascular function in small arteries of the rat - Nourian, Zahra; Hong, Kwangseok; Li, Min; Castorena-Gonzalez, Jorge A.; Martinez-Lemus, Luis A.; Clifford, Philip S.; Meininger, Gerald A.; Hill, Michael A. (Frontiers in Pharmacology, 2023)
Vascular extracellular matrix (ECM) is dominated by elastic fibers (elastin with fibrillinrich microfibrils) and collagens. Current understanding of ECM protein development largely comes from studies of conduit vessels (e.g aorta) while resistance vessel data are sparse. With an emphasis on elastin, we examined whether changes in postnatal expression of arteriolar wall ECM would correlate with development of local vasoregulatory mechanisms such as the myogenic response and endothelium-dependent dilation. Rat cerebral and mesenteric arteries were isolated at ages 3, 7, 11, 14, 19 days, 2 months, and 2 years. Using qPCR mRNA expression patterns were examined for elastin, collagen types I, II, III, IV, fibrillin-1, and -2, lysyl oxidase (LOX), and transglutaminase 2. Elastin, LOX and fibrillar collagens I and III mRNA peaked at day 11 to 14 in both vasculatures before declining at later time-points. 3D confocal imaging for elastin showed continuous remodeling in the adventitia and the internal elastic lamina for both cerebral and mesenteric vessels. Myogenic responsiveness in cannulated cerebral arteries was detectable at day 3 with constriction shifted to higher intraluminal pressures by day 19. Myogenic responsiveness of mesenteric vessels appeared fully developed by day 3. Functional studies were performed to investigate developmental changes in endothelial-dependent dilation. Endothelial-dependent dilation to acetylcholine was less at day 3 compared to day 19 and at day 3 lacked an endothelialderived hyperpolarizing factor component that was evident at day 19. Collectively, in the rat small artery structural remodeling and aspects of functional control continue to develop in the immediate postnatal period.